Design and Field Evaluation of a Smart-Contract FinTech Model for MSME Financial Accountability and Transparency in Medan - Eka Wulandari Surbakti; Siska Hasibuan; Khairunnisa Almadany; Rizaldy Khair (Universitas Medan Area, 2026)
Digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to enhance financial transparency and accountability in order to support Indonesia’s digital economic growth. This research is motivated by the limitations of traditional MSME accounting systems, which are still dominated by manual record-keeping, vulnerable to data manipulation, and characterized by limited access to digital accounting technologies. These conditions may reduce trust from business partners and financial institutions. Blockchain-based smart contract technology offers an innovative solution by enabling transparent, automated, and immutable financial transactions. This study aims to design a smart contract–based digital accounting system suitable for implementation by MSMEs in Medan City. The research adopts a Research and Development (R&D) approach combined with Design Science Research (DSR). The research stages include user needs identification, system design using the Solidity programming language, prototype development on the Ethereum Testnet, and testing through MSME transaction scenarios. System evaluation was conducted through functional testing and end-user interviews, revealing significant improvements in key financial accountability indicators, along with a high system usability score (SUS = 77.12) and strong adoption intention. The proposed system is expected to deliver a real-time, automated, and tamper-resistant accounting model that strengthens MSME financial accountability and competitiveness within the digital economy ecosystem..